As escritas de uma trajetória acadêmica: programa de tutoria e aprendizagem colaborativa no BC&T da UFRN - Macêdo, Julie Idália Araújo (2016)
This study addresses formative aspects of Mentoring Program of the School of Science and Technology of the Federal University of Rio Grande do Norte. The objective of the research was to identify from the academic experiences of the tutors and tutorandos if the training devices adopted by the Mentoring Program legitimize as collaborative learning strategy. For this research, we used a qualitative approach in education, referenced by the theoretical and methodological contributions of narrative research (auto) biographical and the use of the following empirical data collection instruments: conducting narrative interviews and focus groups with tutors and tutorandos. From the stories of the students interviewed were identified five (05) main motivations that lead the program: improving the learning of the contents of the disciplines of physics, computer science and mathematics, our interest in extracurricular activities and improve the curriculum, interest in teaching career, learning space and the need for scholarship. In addition to the motivations, I could identify from the lines of research subjects, 06 (six) factors considered facilitators of collaborative learning and working in successful group. They are: a sense of belonging to the group; mutual aid among members of each group; individual commitment of group members; presence of a leadership group; recognition of the difference in level of knowledge between the group members and affinities of interest. In addition to these factors, we can find four (04) factors identified by students as barriers to such learning. They are the lack of commitment of some colleagues in the group, the lack of participation, the heterogeneity of the group of students and the lack of a physical space for the activities. We conclude that the EC&T Mentoring Program students are the true protagonists of this action. This program is seen as an opportunity for extracurricular studies in which tutors students are seen as mediators in learning and " collaborate " is the word guide the activities. Anyway, before the enablers and inhibiting factors of collaborative learning the Mentoring Program allows students through exchange among peers to build knowledge collectively.